Multifuncionalidade e polissemia do então : um estudo pancrônico - Arena, Ana Beatriz (2008)
According to the linguistic functionalism (Furtado da Cunha, Costa & Cezario, 2003; Hopper, 1987; Neves, 1997), language can only be analized as an object due to use pressure, as a consequence of different communicative situations, in which syntax, semantics and pragmatics are interdependent. Current forms with the same etymology, but different functions and values, are example s that language grammars are under constant transformation, which means that old uses may assume, in a linear and successive way, new functions and values. Based on functional theory, this work aimed, first of all, at showing the stability in the process of grammaticalization of então, since its multifunctional and polissemic character is present since archaic Portuguese. The second aim was to demonstrate that narrative, descriptive, expositive, argumentative and injucntive sequences (Bonini, 2005; Bronckart, 1999) are linguistic contexts that motiva te the multiples values and functions of então, that is, they are inferred in context (Traugott & König, (1991:194). Thus, to achieve the objectives of this study, the panchronic approach turned out to be a methodological possibility, by means of which the evolution of então was studied considering both synchronic and diachronic dimensions. The first step was to make a literature review, in a synchronic perspective, to check how traditional grammars, dictionaries and linguistics discuss então. The second was the reading of texts on functional theory, grammaticalization and on textual genders and types to formulate the theoretical basis of this investigation. After exhaustive data analyses, the research lead to the following results: throughout eight centuries, então behaved as a highly multifunctional and polissemic item. Not only in the archaic period, but also in the modern stage of Portuguese language, então has been used with the following syntactic-semantic values: adverb, logical connector, argumentative operator and sequentiality operator; sometimes, more than one of these values were merged, and in this case então was classified as an imbricated case. As for the motivations to the use of então in the different textual types, there are two polarizations: the uses as adverb and sequentiality operator occurred more frequently in narrative sequences, whereas the uses as logical connector and argumentative operator were predominant in argumentative sequences.